Kajian Parameter Genetik Asal Bahan Tanam Stek Lada Natar-1 Serta Implikasi Terhadap Program Pemuliaan Tanaman - Adawiah; Katartika Fahri, Alamanda (Universitas Muhammadiyah Kotabumi, 2025)
Black pepper (Piper nigrum) is a spice crop with significant potential as an export commodity. In Indonesia, Lampung Province is one of the major production centers contributing to national pepper production after the Bangka Belitung Islands. However, the export potential of black pepper is not aligned with its actual production levels. Strategies to enhance pepper production include the introduction of superior cultivars, such as the Natar 1 variety and vegetative propagation using cuttings sourced from both climbing and fruiting shoots. This study aims to evaluate genetic parameters and the effect of different sources of planting material of the Natar 1, as well as their implications for plant breeding programs. The experimental treatment used a single-case experimental design with three replications, while the experimental layout followed a completely randomized design. The highest genetic variability was observed in the traits of shoot height, number of shoots, number of nodes, and number of roots. Phenotypic variability showed a range of values, categorized as low, moderate, and high. High heritability was recorded for root fresh weight, and planting materials derived from climbing shoots produced higher average values compared to those from fruiting shoots. Estimates of the genotypic and phenotypic coefficient of variability, heritability is important information for plant breeders and have implications for breeding programs, particularly in variety purification and the selection of superior clones. Such information is useful for identifying which plant parts are most effective for propagation, enabling breeders to efficiently multiply superior genotypes and accelerate the development of new varieties.